Elite athletes' perceptions of the effects of illicit drug use on athletic performance - Thomas, J. O.; Dunn, M.; Swift, W.; Burns, L. (Clinical Journal of Sport Medicine, 2010)
Objective: To investigate the perceived risks and benefits that elite athletes associate with illicit drugs and their beliefs concerning the effects of recreational drug use on athletic performance.